2015
DOI: 10.1177/2158244015584378
|View full text |Cite
|
Sign up to set email alerts
|

EU Universities’ Mission Statements

Abstract: In the last 10 years, a highly productive space of metaphor analysis has been established in the discourse studies of media, politics, business, and education. In the theoretical framework of Conceptual Metaphor Theory and Critical Discourse Analysis, the restored metaphorical patterns are especially valued for their implied ideological value as realized both conceptually and linguistically. By using the analytical framework of Critical Metaphor Analysis and procedurally employing Pragglejaz Group's Metaphor I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…Education has been identified as an essential tool for achieving sustainable development across the world [23], as "sustainable education" encourages changes in behavior that create a more sustainable future in terms of environmental integrity, economic viability and just society for present and future generations. "Sustainability education" has been introduced in Agenda 21 of the United Nations (U.N.) document, and the U.N.…”
Section: Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Education has been identified as an essential tool for achieving sustainable development across the world [23], as "sustainable education" encourages changes in behavior that create a more sustainable future in terms of environmental integrity, economic viability and just society for present and future generations. "Sustainability education" has been introduced in Agenda 21 of the United Nations (U.N.) document, and the U.N.…”
Section: Sustainabilitymentioning
confidence: 99%
“…According to many studies, only a few universities include clear sustainability aspects in their mission statements [23,[25][26][27]. Arcimaviciene [23] analyzed the mission statements of 20 European Universities and found that some universities have some features of sustainability in their mission statements.…”
Section: Sustainabilitymentioning
confidence: 99%
“…İngiltere'de de benzer şekilde görev tanımlarının, herkesin rollerinin net olduğu, belirlenen görev tanımının dışına çıkıl-üniversitelerinin misyon ifadelerini analiz ettiği araştırmasında, üniversite fonksiyonları temasında en çok araştırma; amaç ve değerler temasında en çok mükemmellik ve yenilik; rekabet temasında ise liderlik ve öncü olma anahtar kelimelerinin yer aldığı görülen sonuçlar bu araştırmanın bulgusu ile benzerlik göstermektedir. Öte yandan Arcimaviciene (2015) 20 Avrupa üniversitesinin misyon ifadelerini incelediği araştırmasında ifadelerin kişiselleştirme, ticaret, rekabet ve nicelik metaforlarına göre oluşturulduğunu göstermiştir. ABD ve Anglosakson sistemleri yıllardır yükseköğretimde piyasa yönelimini kullanmışlardır.…”
Section: Rol/statü Netliği-karmaşasıunclassified
“…In the contemporary U.S. higher education marketplace, college and university mission statements are profiled on almost every institutional website. The extent to which higher education institution (HEI) mission statements reflect isomorphism, attempts at defining market position or unique "conceptual ideas" (Kosmützky, 2012), and similarly, whether they are primarily aspirational, platforms for strategic implementation and institutional meaning-making, or relevant to the experiences of minoritized students are areas of debate in the international literature (Arcimaviciene, 2015;Cortés-Sánchez, 2018;Ortega et al, 2020;Santa-Ramirez et al, 2022). Thus mission statements are important with respect to organizational behavior (e.g., Othelia Lee, 2010;Serra et al, 2022), human resources practice (e.g., Miller, 1996;Sweem, 2009), leadership for equity (e.g., Lindsay, 1999;Malcom-Piqueux & Bensimon, 2015), student success (e.g., Gnage & Drumm, 2010;Kuh, 2005), and -if education is framed as a human right per the supranational diplomatic architecture -humanitarian engagement (United Nations General Assembly, 1948).…”
Section: Introductionmentioning
confidence: 99%